Safety of intravenous thrombolysis for acute ischemic stroke in patients receiving antiplatelet therapy at stroke onset - Diedler, Jennifer; Ahmed, Niaz; Sykora, Marek; Uyttenboogaart, Maarten; Overgaard, Karsten; Luijckx, Gert-Jan; Soinne, Lauri; Ford, Gary A.; Lees, Kennedy R.; Wahlgren, Nils; Ringleb, Peter A. (Stroke, 2010)
BACKGROUND AND PURPOSE: Antiplatelets (APs) may increase the risk of symptomatic intracerebral hemorrhage (ICH) following intravenous thrombolysis after ischemic stroke. - METHODS: We assessed the safety of thrombolysis under APs in 11,865 patients compliant with the European license criteria and recorded between 2002 and 2007 in the Safe Implementation of Treatments in Stroke (SITS) International Stroke Thrombolysis Register (SITS-ISTR). Outcome measures of univariable and multivariable analyses included symptomatic ICH (SICH) per SITS Monitoring Study (SITS-MOST [deterioration in National Institutes of Health Stroke Scale >or=4 plus ICH type 2 within 24 hours]), per European Cooperative Acute Stroke Study II (ECASS II [deterioration in National Institutes of Health Stroke Scale >or=4 plus any ICH]), functional outcome at 3 months and mortality. - RESULTS: A total of 3782 (31.9%) patients had received 1 or 2 AP drugs at baseline: 3016 (25.4%) acetylsalicylic acid (ASA), 243 (2.0%) clopidogrel, 175 (1.5%) ASA and dipyridamole, 151 (1.3%) ASA and clopidogrel, and 197 (1.7%) others. Patients receiving APs were 5 years older and had more risk factors than AP naïve patients. Incidences of SICH per SITS-MOST (ECASS II respectively) were as follows: 1.1% (4.1%) AP naïve, 2.5% (6.2%) any AP, 2.5% (5.9%) ASA, 1.7% (4.2%) clopidogrel, 2.3% (5.9%) ASA and dipyridamole, and 4.1% (13.4%) ASA and clopidogrel. In multivariable analyses, the combination of ASA and clopidogrel was associated with increased risk for SICH per ECASS II (odds ratio, 2.11; 95% CI, 1.29 to 3.45; P=0.003). However, we found no significant increase in the risk for mortality or poor functional outcome, irrespective of the AP subgroup or SICH definition. - CONCLUSIONS: The absolute excess of SICH of 1.4% (2.1%) in the pooled AP group is small compared with the benefit of thrombolysis seen in randomized trials. Although caution is warranted in patients receiving the combination of ASA and clopidogrel, AP treatment should not be considered a contraindication to thrombolysis.